Biological therapies in patients with liver disease: are they really lifesavers?. (3rd April 2022) - Vitale, Giovanni; Gitto, Stefano; Campani, Claudia; Turco, Laura; Baldan, Anna; Marra, Fabio; Morelli, Maria Cristina
ABSTRACT: Introduction: The liver plays a key role in the setting of immune tolerance. Targeting antigens for presentation by antigen-presenting cells in the liver can induce immune tolerance to either autoantigens from the liver itself or organs outside of the liver. Despite its non-conventional capacity for tolerance induction, the liver remains a target organ for autoimmune diseases. Whereas chronic inflammation and intra-hepatic immuno-suppressive microenvironment occurring during liver fibrosis lead to hepatocellular carcinoma. Monoclonal antibodies have revolutionized the therapeutic strategies of many autoimmune diseases and some cancers. Areas covered: We review data from literature regarding the safety and efficacy of biologics in treating hepatobiliary autoimmune diseases and primary liver cancers. Furthermore, we describe their potential use in the setting of liver transplants and their main immune-related liver adverse events. Expert opinion: Biological therapies have changed the natural history of main autoimmune diseases and solid cancers. Compared to other organs and disease settings, the liver lags behind in biologics and their applications. The development of novel diagnostic and therapeutic strategies based on the immunological and antigenic characteristics of the hepatobiliary system could reduce mortality and transplant rates linked to chronic liver diseases.